Breaking Point: The Last Serve Against the Human Brain - Cardenas Castro, Hernan Steven (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Mental health is a breaking point among tennis players. Even the greatest tennis players have realbreaking points in life, for example, Djokovic with his anger attacks, Naomi Osaka dealing withdepression, and Mardy Fish with anxiety and heart attacks after retirement. As human beings, mastersor learners, no one is excluded from the battle against our brain.